GRAMMATICAL PROBLEMS OF TRANSLATION - Irodaxon Egamberdiyeva; Giyosiddin Ibragimov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Translation is a complex process that involves transferring meaning from one language to another. In the case of English and Russian, there are numerous grammatical challenges that translators face when translating between the two languages. This article explores the grammatical problems of translation in terms of English and Russian, and examines some of the quotes related to translation, particularly Russian English translation